Three-dimensional modelling of a multi-span masonry arch bridge: Influence of soil compressibility on the structural response under vertical static loads. (15th October 2020) - Zani, Giulio; Martinelli, Paolo; Galli, Andrea; di Prisco, Marco
Highlights: An historical multi-span masonry arch bridge under vertical loads is investigated. FEM models without soil nonlinearity may underestimate the vertical displacements. Numerical models without SSI can underestimate the damage level in the bridge. Differential settlements affect the structural capacity of massive bridges. Abstract: The paper presents the results of an experimental and numerical study aimed at investigating the structural response of a historical multi-span masonry arch bridge. The bridge, named Azzone Visconti bridge, was built in the 14th century and is placed in northern Italy. The bridge behaviour under static loads was checked by means of a sequence of acceptance load tests designed accordingly to the provisions of the Italian Code. A detailed 3D finite element model was built based on previous extensive geometric survey, historical data and mechanical characterization of both the soil constituting the riverbed and the stone masonry constituting the piers. Three different models describing the mechanical behaviour of the foundations have been implemented to include soil-structure interaction. A comparison between the experimental measures obtained during the acceptance load tests and the numerical results has allowed establishing the reliability of the models. Post-test nonlinear finite element analyses have allowed the evaluation of the bridge mechanical behaviour under vertical static loads. The influence of the different soil-structure interaction models adopted in the analyses on the evaluation of the bridge structural response is widely discussed.